2022
DOI: 10.1136/bmjopen-2021-054574
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity and mortality patterns of preterm low birthweight neonates admitted to referral hospitals in the Amhara region of Ethiopia: retrospective follow-up study

Abstract: ObjectiveThis study aimed to assess the morbidity and mortality patterns of preterm neonates with low birth weight admitted in the Amhara region referral hospitals in Ethiopia.DesignHospital-based retrospective follow-up study.SettingAmhara region referral hospitals, Ethiopia.ParticipantsA total of 291 preterm neonates low birth weight that were admitted to referral hospitals in the Amhara region between 1 January 2017 and 30 December 2018 were reviewed. Data were entered into Epi-data V.4.4.2.1 and exported t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
1
2
1
Order By: Relevance
“…Accordingly, this study found that at the end of the follow-up 47.16% (95% CI 42.80% to 52.55%) of neonates developed RDS. This finding was aligned with studies conducted in Thailand (44.15%),37 and Ethiopia 49.8 3%,38 The possible justification is due to similarities in study design, sample size and the presence of similar maternal health problems. On the other hand, this study was higher than two different studies conducted in Pakistan 11%–12.8%,15 16 India 38%,39 Nepal 21.4%40 and Nigeria 10.9% 19.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Accordingly, this study found that at the end of the follow-up 47.16% (95% CI 42.80% to 52.55%) of neonates developed RDS. This finding was aligned with studies conducted in Thailand (44.15%),37 and Ethiopia 49.8 3%,38 The possible justification is due to similarities in study design, sample size and the presence of similar maternal health problems. On the other hand, this study was higher than two different studies conducted in Pakistan 11%–12.8%,15 16 India 38%,39 Nepal 21.4%40 and Nigeria 10.9% 19.…”
Section: Discussionsupporting
confidence: 83%
“…Due to this, the synthesised surfactant is not adequate to maintain alveolar stability, and this leads to atelectasis, and the neonate develops RDS 32 33 50. In addition, premature neonates are more vulnerable to different medical problems such as hypothermia, hypoglycaemia, sepsis, NEC and other comorbidities while this increases the probability of developing RDS 38 42…”
Section: Discussionmentioning
confidence: 99%
“…The discrepancy was reportedly caused by a variation in the discharge criteria and the determination of fetal viability in our setting (> 28 weeks). a research done on morbidity and mortality patterns of preterm low birthweight neonates admitted to referral hospitals in the Amhara region in Ethiopia showed mean length of hospital stay was 9.82 days which was lower than this study (9). This was because the study participant included in the study were low birth weight preterm neonates (birth weight < 2500gm) and the sample size was also larger as compared to the current study.…”
Section: Discussioncontrasting
confidence: 70%
“…Studies also showed as length of hospital stay of preterm neonate increased the hazard of time to death (8). On the other hand, when a very low birth weight preterm neonate stayed less than the median length of hospital stay, there would be associated increase mortality (9). Some studies showed prolonged and continuous exposure to noise and bright lights for preterm neonates had a negative impact on future neurocognitive development (10,11).…”
Section: Introductionmentioning
confidence: 99%